The Role of Auditor Behavior in Moderating Independence, Time Pressure, Experience that Affects Audit Quality at Public Accounting Firms - Asen Susanto; Erlina; Chandra Situmeang; Abdillah Arif Nasution (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
An audit is a systematic, independent examination of financial statements, accounting records, and supporting documents prepared by management, the purpose of which is to form an opinion on the accuracy of financial statements. Financial statements must have relevant characteristics (reliability) and reliability (reliability). Without the services of auditors, management cannot convince outsiders that the financial statements presented by management contain reliable and reliable information. Independence is the auditor's attitude to impartiality. The experience of the examiner contributes to high-quality inspection. The purpose of this study is to analyze the influence of auditor behavior, time pressure, audit experience, and independence on audit quality. The research was conducted at a Public Accounting Firm (KAP) in Medan City. The number of research samples of 80 people was selected by the nonprobability sampling method. Data collection was carried out by questionnaire through Google form and literature studies that supported this study. The method used in this study is to use the Structural Equation Model (SEM) equation using the Partial Least Square (PLS) tool version 3.0. PLS consists of external relationships (outer model) and internal relationships (inner model), cross-loading> 0.7, Composite Reliability, Convergent Validity, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). Based on the results of the analysis, it was found that the first, second, fourth, and seventh hypotheses were rejected where each variable such as auditor behavior, and time pressure, did not affect audit quality and independence could not moderate the influence between auditor behavior on audit quality, independence could not moderate audit quality. The third, fifth, and sixth hypotheses are accepted where each variable such as audit experience, independence moderates the effect of time pressure on audit quality, and independence moderates the effect of audit experience on audit quality.